Prevalence of Bacteria and their Sensitivity to Various Antibiotics in Chronic Suppurative Otitis Media (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to find out the most common strains of bacteria encountered in chronic suppurative otitis media and their sensitivity to various antibiotics.Study Design: Retrospective, analytic studyPlace and Duration of Study: This study was conducted on out patients presenting to ENT department at Liaquat University Hospital Hyderabad, Sindh- Pakistan from January 2011 to June 2011.Materials and Methods: This study was conducted jointly at ENT Unit II in collaboration with Oral and Maxillofacial surgery Department LUMHS with the help of microbiology laboratory of Liaquat University Hospital, Hyderabad, Sindh, Pakistan. The study was conducted for the period of 6 month A total of hundred samples of ear discharges were collected and analyzed for bacterial growth; and sensitivity towards various antibiotics were determined by using standard microbiological techniques using disc diffusion method.Results: Among hundred patients, 59% were male and 41% females. Age of patients varied from 2 to 60 years. There were different species of bacteria isolated. Pseudomonas aeruginosa (46%) was the most frequent organism followed by staph aureus (27%) and proteus (27%). The prevalence of gram negative bacterium was greater than gram positive. Among the antibiotics, ciprofloxacin and enoxacin were found to be the most effective against these organisms.Conclusion: Early and precise diagnosis of infective disease of ear is decisive in order to administer the correct antibiotic therapy and avoid complications.